PENJADWALAN PREVENTIVE MAINTENANCE KOMPONEN KRITIS MESIN VACUUM MIXER DENGAN PENERAPAN SIMULASI MONTE CARLO PADA PT. X - Muhammad Rizal (2021)
PT. X is an industry engaged in the pharmaceutical sector. There are many main production facilities, especially on machines used by this industry, one of which is a Vacuum Mixer machine. The Vacuum Mixer machine was the machine with the highest downtime in 2020 with a total downtime of 38 hours. If the value of downtime is high and this problem continues, many productions may be late, of course, this will greatly affect the production schedule and result in losses for the company, therefore an optimal machine maintenance schedule is needed. To implement an optimal maintenance schedule, research was carried out by designing the maintenance of the Vacuum Mixer machine component by simulating the damage that would occur using the Monte Carlo Simulation method and redesigning the preventive maintenance schedule to reduce the value of downtime that occurred. The purpose of this study is to determine the critical components of the Vacuum Mixer machine using FMEA, determine the value of machine reliability, and determine preventive scheduling using Monte Carlo Simulation. From the results of FMEA critical components are components of the Gearbox and Turbine Mixer. The reliability values of the Vacuum Mixer machine components are 85.5% and 85% with the MTTF of the Gearbox component every 8 days and the Turbine Mixer component every 15 days. The results of the reliability efficiency of the Gearbox component are 35.5% and the Turbine Mixer component 35%